1993
DOI: 10.1016/s0006-3495(93)81497-8
|View full text |Cite
|
Sign up to set email alerts
|

New physical concepts for cell amoeboid motion

Abstract: Amoeboid motion of cells is an essential mechanism in the function of many biological organisms (e.g., the regiment of scavenger cells in the immune defense system of animals). This process involves rapid chemical polymerization (with numerous protein constituents) to create a musclelike contractile network that advances the cell over the surface. Significant progress has been made in the biology and biochemistry of motile cells, but the physical dynamics of cell spreading and contraction are not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
3
27
1
Order By: Relevance
“…As suggested by others [see review by Bereiter-Hahn and Luers, 19941, the tail contraction would also be expected to pull the rear of the cell forward toward the leading lamella and simultaneously drive the cytosolic fluid through the cytoskeletal matrix of the lamella, adding material to the leading edge. Growth of the actin cytoskeleton at the leading edge and simultaneous disassembly throughout the lamella and at the junction between the leading lamella and the nuclear mound complete the processes necessary for operation of a complete causative cycle in this model [Evans, 1993;Condeelis, 19931. The absence of significant tractions under the leading lamella and also near the trailing edge could be explained by invoking the near cancellation of the major contributions acting in these regions (see above).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by others [see review by Bereiter-Hahn and Luers, 19941, the tail contraction would also be expected to pull the rear of the cell forward toward the leading lamella and simultaneously drive the cytosolic fluid through the cytoskeletal matrix of the lamella, adding material to the leading edge. Growth of the actin cytoskeleton at the leading edge and simultaneous disassembly throughout the lamella and at the junction between the leading lamella and the nuclear mound complete the processes necessary for operation of a complete causative cycle in this model [Evans, 1993;Condeelis, 19931. The absence of significant tractions under the leading lamella and also near the trailing edge could be explained by invoking the near cancellation of the major contributions acting in these regions (see above).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several attempts to model the underlying physical processes in cell motility by using continuum mechanics approaches (23)(24)(25). However, quantitative measurements of the cellular traction forces are still challenging because of the necessary temporal and spatial resolutions.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Recent studies have also shown that cells from multicellular organisms, such as leukocytes, zebrafish primordial germ cells and selected tumor cells, also exhibit amoeboid-like movements. The amoeba migrates via a sterotypic manner by extending its pseudopodia forward and coordinating cytoplasmic streaming.…”
Section: Introductionmentioning
confidence: 99%